If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+3)-6=15-4x-9+8x
We simplify the equation to the form, which is simple to understand
4(x+3)-6=15-4x-9+8x
Reorder the terms in parentheses
+(+4x+12)-6=15-4x-9+8x
Remove unnecessary parentheses
+4x+12-6=+15-4x-9+8x
We move all terms containing x to the left and all other terms to the right.
+4x+4x-8x=+15-9-12+6
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| 2x+n=210 | | -7+(-3)x+5+(-6)x= | | 0.18(y-8)+0.08y=0.06y-0.09(30) | | 6w-2w=44 | | 5(x+4)=3x-2(4) | | 5x^2-40+75=0 | | 0.50x+0.45(70)=0.25(114) | | -6(x-2)=3(x+14) | | 5/12+a=11/12 | | 20+n=1 | | 40t+55x= | | 1.5+0.3r=-4.2 | | 4-5k=-4k+7 | | 15y-3x=-6 | | a=400+(-80)(1-1) | | x+12=17-4x | | 160+0.25n=342.50 | | 6(3x-2)=3x+5x | | 10x-25=625 | | x/10-5/2+x=3x/5 | | 3n+1=5n+8 | | 4(m+3)=44 | | 2x+4259=210355 | | 2(x-8)=10 | | 9x+6y=18 | | -2y=4-6x | | 2(3x-1)=4x+5 | | 5(x+5)=64 | | 3(2f-6)+6=36 | | 3n+2(4n-5)-7+n= | | -6x+2x=3x | | x=6x^7+35x^6-169x^5-612x^4+1823x^3+1215x^2-2758x-980 |